2013
DOI: 10.21608/jppp.2013.87301
|View full text |Cite
|
Sign up to set email alerts
|

CERTAIN ECOLOGICAL ASPECTS FOR Icerya seychellarum (Westwood) ON COFFEE PLANTS Coffea arabica IN EGYPT

Abstract: Certain ecological aspects of the Seychellarum mealybug, Icerya seychellarum (Westwood) which is considered as a key pest on coffee trees, a promising newly crop cultivated in Egypt, have been investigated under two different ecosystems throughout two years, 2009 & 2011. Results revealed that this mealybug species was found all the year round in both localities. The total population recorded four peaks of seasonal abundance in both investigated ecosystems on coffee trees and it passed through three overlapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…On the other hand, the relative humidity gave an insignificant positive effect during the fall, winter and summer. Many authors showed the same effects of meteorological parameters on the population activities of mealybugs, Nabil, et al, (2013) and Raut, et al, (2013).…”
Section: E) Effect Of the Natural Enemiesmentioning
confidence: 76%
“…On the other hand, the relative humidity gave an insignificant positive effect during the fall, winter and summer. Many authors showed the same effects of meteorological parameters on the population activities of mealybugs, Nabil, et al, (2013) and Raut, et al, (2013).…”
Section: E) Effect Of the Natural Enemiesmentioning
confidence: 76%